A scoping review of non-communicable diseases and maternal and child health needs of Venezuelan migrants in South America - Benjamin Gallo Marin; Andres Amaya; Giancarlo Medina Perez; Adam C. Levine; Katelyn Moretti; Stephanie C. Garbern (Journal of Global Health Reports, 2021)
# Background